Human behaviour factors influenced the risk of typhoid infection in Pasir Mas Kelantan - Kamariah Hussin,; Md Idris Md. Nor ,; Osman Ali, (Universiti Kebangsaan Malaysia, 1997)
A case control study was carried out in the district of Pasir Mas with the aim of determining the relationship between human behaviour which is reflected through their practices with the risk of typhoid infection. Respondents consisted of 87 cases and 87 controls who fulfilled the study criteria. Data were obtained from guided questionnaires and observations of the respondents' home environment. Scores were given for knowledge and practices under study. Results of univariate analysis showed that the only significant difference between cases and controls was the mean score of their knowledge on typhoid i.e. the mean score for cases was 17.2±1:3.3 while controls had a mean score of 15.6±1:4.4 (p<0.05). There was also a significant association between knowledge on typhoid with the risk of typhoid infection (OR 0.26 CI 95% 0.09-0.69). Multiple logistic regression however showed significant relationships between knowledge (OR 0.28 CI 95% 0.11-0.71), personal hygience practices (OR 0.21 Cl 95% 0.04-0.92) as well sanitary use of latrines (OR 4.97 CI 95% 1.12-21.54) with the risk of typhoid infection. Effective health education in its many forms still remains as an important strategy for the preventation and control of typhoid infection.